Research-Based Laboratory Promotes Student-Learning Skills and Enhances Undergraduate Research Experience - Choudhary, Madhusudan; Johnson, Hannah (IJRDO- Journal of Educational Research, 2016)
Research experience, at the undergraduate level, is important in understanding the scientificprocess. However, employment and adaptation of research-based laboratory has beenchallenging to apply in a large class setting as well as being effective in properly exposingstudents to core concepts in genetics covered during the lecture. This paper describes howanalysis of the ctrA gene, which encodes a master cell-cycle transcriptional regulator forbacterial cell-cycle regulation, was adapted and incorporated into the laboratory component of anundergraduate Introductory Genetics course. A total of 159 students participated in this projectover a three-semester period, and was carried out with approval from the Institutional ReviewBoard. The test-instrument consisted of collaborative and critical thinking questions dealing withcore principles of genetics. Pre-test and post-test scores were compared to assess studentlearningand overall effectiveness of the proposed curriculum in light of course objectives. Theresults validate that the research based laboratory approaches not only broadens student-learningskills their understanding of core concepts in genetics, but also provides the necessary technicalskills to carry out independent research projects.